Behavioral factors in hotel location: A study of hotels from Opole Province in Poland - Puciato, Daniel (Turyzm/Tourism, 2020)
The choice of location is one of the key economic decisions for hotel owners. In modern economics traditional premises are increasingly questioned, and assumptions are often made involving imperfect competition, limited rationality of behavior, and the incomplete scope of information or the inability to use it effectively. This is also reflected in the theory of location within which a behavioral trend has been developed assuming the occurrence of non-economic, subjective factors in making location decisions. The aim of the paper is to identify behavioral factors in hotel location in Opolskie Province in Poland. The paper uses four main research methods: literature review, documentation, diagnostic survey and individual case studies. The study results confirm the importance of the behavioral approach in the process of selecting a location for independent hotels in Opolskie Province, involving the choice of secondary or primary locations. In the latter case, the decision-making process is based entirely on behavioral factors or is supplemented by them in situations where an objective approach is not connected with decision-making certainty. Behavioral factors such as intuition, emulation, experience, place of origin and residence, individual cases and the influence of others should be regarded as highly significant.